EXISTENTIAL STRUGLE OF GERMAN LANGUAGE TOU GUIDE IN PT. NUSA DUA BALI TOUR AND TRAVEL, TUBAN, BADUNG - Artajaya, Made; Mudana, I Gede (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2019)
The growth of new tour and travel agents in Bali targeting the tourist market from Germany has created intense competition among travel bureaus. This causes a decrease in the number of German tourists who use the services of a travel agency PT. NDBT. The purpose of this study was to analyze the existential struggle that occurred at PT NDBT conducted by German-speaking guides. The research problems are 1) how the hegemony and counter hegemony that occurred in PT. NDBT, the factors causing and the implications for the PT NDBT. This study uses a qualitative method. Data collection techniques used were observation, interviews, and documentation studies. The theory used is the theory of hegemony, social practice theory and the theory of communicative action in an eclectic manner. The results showed that the existential struggle carried out by German guides on the corporate hegemony practice of PT. NDBT against guides as a coordinated party is a counter hegemony. Supporting factors for the German-speaking touristic licensing struggle is the decline in the number of German tourists using PT.NDBT services in Bali. As a result, the implication posed by the existential struggle is the desire to stimulate themselves in carrying out scouting work. In addition, guides must also increase knowledge of the German language and knowledge of the field of guidance. Existential struggle also has implications for the meaning of communication for fellow German tour guides. Keywords: existential struggle, German tour guides, tourists, Germany, travel agency.